Shewhart Chart Analysis And Its Application In Educational Quality Control: Literature Review - Rizki, Aprilia; Lestari, Widia Dwi; Madhakomala, R. (Journal Coaching Education Sports, 2024)
In the context of increasing demands for quality assurance and continuous improvement in education, Shewhart charts, originally developed for industrial processes, have found applications beyond manufacturing. Shewhart control charts, also known as statistical process control (SPC) charts, serve as valuable tools for monitoring and controlling processes by distinguishing between common and special cause variation. This literature review explores the application of Shewhart charts in the field of educational quality control, highlighting their potential to improve decision-making processes, identify trends, and enhance educational outcomes.